Quiste renal simple infectado: caso clínico y revisión de la literatura - Fernández R., Mauricio; Novoa M., Catalina; Rodríguez E., Andrea; Cortés S., Esteban (Revista Hospital Clínico Universidad de Chile, 2007)
We describe a case of a 29 years old woman with an infected simple renal cyst in which no etiologic agent was found. The diagnose was made by cystic fluid aspiration. Antibiotic therapy by itself was not enough to control the infection and a percutaneous drainage was performed with rapidly normalization of the inflammatory parameters. The case is presented and a literature review on simple renal cyst is made.